UJI ANTAGONISME ISOLAT FUNGI ENDOFIT DARI DAUN NAMNAM (Cynometra cauliflora L.) TERHADAP Candida albicans, Malassezia furfur SECARA IN VITRO - Hamtini, Hamtini; Rahmawati, Nurmeily; Anliza, Syarah (Jurnal Medikes (Media Informasi Kesehatan), 2024)
The use of traditional medicine as an option for treatment is an alternative that is in great demand because traditional medicine has been proven to be relatively safe if used correctly and with the right indications and rarely causes side effects. This is one of the factors for people to use natural ingredients or traditional medicine as an alternative treatment. One of these efforts is to explore and find antioxidant compounds such as beta carotene, astasantine, alkaloids and phenols in plants. To take bioactive compounds directly from the plant, a lot of biomass or parts of the plant are needed, so to make the method of obtaining these bioactive compounds more efficient, specific endophytic microbes obtained from the inside of the plant are used which are expected to be able to produce a number of bioactive compounds from the plant. Endophytic microbes consist of bacteria, fungi and actinomycetes which have the potential to produce bioactive compounds such as those produced by plants without causing damage to the plant. The aim of this research was to examine the antagonism ability of the Namnam leaf endophytic fungus (Cynometra cauliflora L.) against pathogenic fungi. The stages of the research method are identification of endophytic fungi macroscopically and microscopically and inoculation of endophytic fungi into PDA media, followed by preparation of test pathogenic fungi, the pathogenic fungi tested are Candida albicans and Malassezia furfur, antagonism test by inoculating pathogenic fungi into PDA media and After that, place the endophytic fungi on media that has been inoculated with pathogenic fungi, incubate at room temperature for 3-5 days and measure using a ruler. The results of macroscopic and microscopic identification of endophytic fungi, isolate code P1-1, were Penicillium sp, while isolate codes P4-1 and P5-1 were identified as Mucor sp. Based on the antagonist test that was carried out, it was seen that endophytic fungi grew in the test media but did not provide significant inhibition to the growth of the test fungi, namely Candida albicans and Malassezia furfur.